FinTech women walk the talk - Edwards-Dashti, Nadia (Palgrave Macmillan, 2022)
The FinTech community is steeped in change and has the potential to pave the way for equal opportunities in the workplace, considering the positive actions that have taken place. There is so much more that can be done but what has been achieved so far needs to be replicated. This book showcases the successes in the industry alongside that which could act as a barrier or escalator. Being the first of its kind, FinTech Women Walk the Talk draws upon the author’s podcasts that feature the insights of more than 150 FinTech experts; more than 100 of which are women. It is a call to action for diversity in the workplace, showcasing the successes and presenting how to overcome the challenges. By demystifying FinTech, and highlighting its potential to drive change, this book explores how to achieve gender parity in the workplace. The FinTech industry is used as a case study and hence of interest to practitioners in finance, technology, FinTech and beyond
Keywords: Finanztechnologie; Innovation; Finanzdienstleistung; Arbeitsbedingungen; Weibliche Arbeitskräfte; Gleichberechtigung; Women in finance; Financial services industry / Technological innovations; Sex discrimination in employment